Bifurcation stenting on the background of an aneurysm of the anterior descending artery - R. E. Kalinin; I. A. Suchkov; A. V. Karpov; I. B. Ilyasov; I. N. Shanaev (Сибирский научный медицинский журнал, 2023)
A case report of a combination of an aneurysm of the anterior descending artery in the area of the departure of the diagonal branch and two coronary-ventricular fistulas has been described. The patient was stented earlier (in 2019 – the anterior descending artery and diagonal branch and in 2020 – the circumflex artery) for stable angina pectoris. However, in 2022, she was admitted to the hospital with a diagnosis of “ST-segment elevation myocardial infarction” and a coronary angiography revealed thrombosis of both the aneurysm cavity of the anterior descending artery and previously stented segments of the anterior descending artery. As an emergency, the patient underwent provisional stenting with final kissing balloon dilation, as a result of which the lumens of the anterior descending artery and the diagonal branch were completely restored, and the aneurysm cavity was not contrasted due to its embolization by thrombotic masses.